Three‐dimensional conformal radiation therapy alone for esophageal squamous cell carcinoma: 10‐year survival outcomes. Issue 3 (16th January 2019) - Fan, Xing‐Wen; Wu, Jun‐Lan; Wang, Hong‐Bing; Liang, Fei; Jiang, Guo‐Liang; Wu, Kai‐Liang
Abstract : Background: Concurrent chemoradiation is the standard treatment for locally advanced esophageal squamous cell carcinoma (SCC). We conducted a phase II study to explore the effect of three‐dimensional conformal radiotherapy (3‐DCRT) alone for patients with locally advanced esophageal SCC. This study aimed to analyze the long‐term survival outcomes. Methods: Between November 2004 and April 2007, 30 patients with thoracic esophageal SCC underwent late‐course sequential boost 3‐DCRT at Fudan University Shanghai Cancer Center. The planning target volume (PTV1) comprised a 1.2–1.5 cm lateral margin around the gross tumor volume and a 3.0 cm margin, superior and inferior to the gross tumor volume. PTV2 encompassed the gross tumor volume with a margin of 0.5–0.7 cm. The PTV1 dose delivered was 50 Gy, and the PTV2 dose was a boost dose of 16 Gy, resulting in a total dose of 66 Gy. No chemotherapy was administered. Results: The median follow‐up time was 30 months for all patients, and 132 months for patients who were alive. The median overall survival was 27 months (95% confidence interval [CI] 18.9–35.0). The 2‐, 5‐, and 10‐year overall survival rates were 56.6%, 33.3%, and 26.6%, respectively. The median progression‐free survival was 14 months (95% CI 7.7–20.2 months), and the 2‐, 5‐, and 10‐year progression‐free survival rates were 33.3%, 30.0%, and 26.6%, respectively. No severe late toxicity was observed in long‐term survivors. Conclusion: Late‐course sequential boost 3‐DCRT is safe and feasible with promising long‐term outcomes for esophageal SCC.